Sport-specific musculoskeletal growth and postural control in female artistic gymnasts: a 12 month cohort study - Wyatt, H. E.; Gittoes, M. J. R.; Irwin, G. (Sports Biomechanics, 2020)
Female gymnasts have been evidenced to experience sport-specific growth, of which broad shoulders and narrow hips are common characteristics. In addition to being a central component of handstand performance, postural control mechanisms, including whole-body and lumbo-pelvic stability, have been identified as risk factors for overuse spinal pathology. The study aimed to develop a fundamental understanding of musculoskeletal growth and postural control responses of female artistic gymnasts in order to extend longitudinal insights into overuse spinal pathology risk. Whole-body anthropometric measures were collected for 12 competitive female gymnasts (age at recruitment: nine to 15 years) at three time points across a 12 month period. Musculoskeletal growth was partially defined as the rate of bicristal-to-biacromial breadth ratio development, and informed shoulder- and pelvis-dominant growth sub-groups. Kinematic and kinetic indicators of postural control were determined for a total of 700 handstand trials. The shoulder-dominant (gymnastics-specific) growth group was found to have significantly greater biomechanical risk for general stability (p < 0.001) than the pelvis-dominant group. Significantly greater lumbo-pelvic risk was demonstrated for the pelvis-dominant group (p < 0.001). Extended idiosyncratic examination of proportional sport-specific growth measures alongside multi-faceted risk monitoring was advocated for the effective development of future overuse pathology prevention protocols.